Psychotherapy in the Private Sector: A Survey of Licensed Psychologists and Psychotherapists in Quebec - Bradley, Stacy; Roberge, Pasquale; Service, John; Vasiliadis, Helen-Maria; Drapeau, Martin (Canadian Journal of Counselling and Psychotherapy, 2019)
Many clients and patients seek mental health services, including psychotherapy, in the private sector. However, there is a lack of information concerning the characteristics of private psychotherapy practice. With an increased focus on access to mental health care, knowledge of this sector is needed. This study aimed to document the current characteristics of practitioners who offer psychotherapy services in the private sector in Quebec. Participants included 671 psychologists and psychotherapists. Results indicated that the most commonly served age population was adults, the average number of sessions was 23.35 (SD = 20.82), and the average fee for individual therapy was $95.10 (SD = $16.69). Data are also reported on the types of services offered, practitioners collaboration with other professionals, the conditions treated, the use of various clinical tools, and new trends in the field. Implications of the results for practitioners, trainees, and policy developers are discussed.